Tumor-Derived Exosomes Modulate Primary Site Tumor Metastasis - Bai, Suwen; Wang, Zunyun; Wang, Minghua; Li, Junai; Wei, Yuan; Xu, Ruihuan; Du, Juan (Frontiers in Cell and Developmental Biology, 2022)
Tumor-derived exosomes (TDEs) are actively produced and released by tumor cells and carry messages from tumor cells to normal or abnormal cells residing at close or distance sites. TDEs participate in every process of tumor metastasis. In this review, we explore the entire behavior of exosomes action during tumor metastasis. In principle, TDEs transport tumor-derived proteins and non-coding RNAs to their own tumor cells and promote migration properties. Transport to normal cells ,such as vascular endothelial cells and immune cells and so on, promoting angiogenesis, inhibit the activation of immune cells and improve the tumor implantation environment. In a word, TDEs make all factors contribute to the formation of tumor metastasis. We thus intend to summarize the function of TDEs and their components in whole process of tumor metastasis and illuminate shortcomings for advancing research on TDEs in tumor metastasis.